2019
DOI: 10.1055/s-0039-3402023
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition Therapy for an Achondroplastic Patient: Case Report

Abstract: Introduction Achondroplasia is the most common form of dwarfism in humans. At the end of the twentieth century, achondroplasia had its natural history investigated and its morbimortality understood. In dwarves, obesity is one of the causes of morbidity, and it is difficult to evaluate it due to the great disproportion among anthropometric data. The characterization of the nutritional needs of these patients represents an interesting dilemma for physicians. In view of these difficulties, the present case report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Tables 1 and 2 summarize the key characteristics from those studies that reported at least one patient-important or economic outcome. Regarding study design, four were case series [ 26 , 34 , 35 , 73 ], 24 cross-sectional studies [ 5 , 6 , 24 , 29 , 36 – 38 , 40 , 45 , 48 , 50 54 , 56 , 58 , 60 , 61 , 66 , 69 , 70 , 72 , 75 ], and 25 case reports [ 27 , 28 , 30 – 33 , 39 , 41 – 44 , 46 , 47 , 49 , 55 , 57 , 59 , 62 – 65 , 67 , 68 , 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 summarize the key characteristics from those studies that reported at least one patient-important or economic outcome. Regarding study design, four were case series [ 26 , 34 , 35 , 73 ], 24 cross-sectional studies [ 5 , 6 , 24 , 29 , 36 – 38 , 40 , 45 , 48 , 50 54 , 56 , 58 , 60 , 61 , 66 , 69 , 70 , 72 , 75 ], and 25 case reports [ 27 , 28 , 30 – 33 , 39 , 41 – 44 , 46 , 47 , 49 , 55 , 57 , 59 , 62 – 65 , 67 , 68 , 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four of the included studies were conducted in Brazil [ 5 , 24 , 26 – 34 , 36 , 38 – 40 , 45 , 49 , 57 , 63 , 66 , 67 , 69 , 74 , 75 ], nine in Argentina [ 44 , 50 54 , 56 , 64 , 73 ], five in Colombia [ 42 , 48 , 58 , 68 , 71 ], four in Mexico [ 35 , 37 , 41 , 59 ], three in Chile [ 46 , 47 , 61 ], three in Cuba [ 43 , 60 , 65 ], one each in Dominican Republic [ 55 ], in Paraguay [ 62 ], in Venezuela [ 72 ], and in Puerto Rico [ 70 ]. Only one article [ 6 ] was a multicenter cross-sectional study, which involved nine countries (i.e., Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Uruguay, and Venezuela) [ 6 ].…”
Section: Resultsmentioning
confidence: 99%